Hindi, asked by brieshbrijesh75, 6 months ago

a=2+√3 and 1/a of value​

Answers

Answered by amanraza786
0

Answer:

Here is the answer you were looking for:

\begin{gathered}a = 2 + \sqrt{3} \\ \\ \frac{1}{a} = \frac{1}{2 + \sqrt{3} } \\ \end{gathered}

a=2+

3

a

1

=

2+

3

1

On rationalizing the denominator we get,

\begin{gathered} \frac{1}{a} = \frac{1}{2 + \sqrt{3} } \times \frac{2 - \sqrt{3} }{2 - \sqrt{3} } \\ \end{gathered}

a

1

=

2+

3

1

×

2−

3

2−

3

Using the identity :

(x + y)(x - y) = {x}^{2} - {y}^{2} (x+y)(x−y)=x

2

−y

2

\begin{gathered} \frac{1}{a} = \frac{2 - \sqrt{3} }{ {(2)}^{2} - {( \sqrt{3} )}^{2} } \\ \\ \frac{1}{a} = \frac{2 - \sqrt{3} }{4 - 3} \\ \\ \frac{1}{a} = 2 - \sqrt{3} \\ \\ a - \frac{1}{a} \end{gathered}

a

1

=

(2)

2

−(

3

)

2

2−

3

a

1

=

4−3

2−

3

a

1

=2−

3

a−

a

1

Putting the values,

\begin{gathered}a - \frac{1}{a} = (2 + \sqrt{3} ) - (2 - \sqrt{3} ) \\ \\ a - \frac{1}{a} = 2 + \sqrt{3} - 2 + \sqrt{3} \\ \\ a - \frac{1}{a} = \sqrt{3} + \sqrt{3} \\ \\ a - \frac{1}{a} = 2 \sqrt{3} \end{gathered}

a−

a

1

=(2+

3

)−(2−

3

)

a−

a

1

=2+

3

−2+

3

a−

a

1

=

3

+

3

a−

a

1

=2

3

Hope this helps!!!

Answered by SrijaMahendrakar
0

Answer:

Hope it's Helpful for you

Attachments:
Similar questions